LEARNING BASED ON ENVIRONMENT AS STIMULUS TO THINK CRITICAL IN LEARNING THE INDONESIAN LANGUAGE IN THE 3T AREA - Erwin Erwin (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2018)
There has been a tremendous jump in the dynamics of learning in the 21st century Era today. Innovation of learning increasingly experienced development, ranging from digital, online, blended, multimodal, and some other innovations created as an alternative that is deemed to overcome learning difficulties in education. This paper is presented as an affirmation, that there are exceptions that must be adjusted to the learner in the 3T area, due to the lack of educational infrastructure. Therefore, the innovation of environment-based learning can be an alternative as a stimulus to hone students thinking crisis in learning Indonesian. This paper presents some important points, namely: (1) Learning Indonesian Phenomenon. (2) Problem of Indonesian Language Learning in 3T Areas. (3) Environment Learning and Environmental Use in Learning. (4) Critical Thinking with Environmental-Based Learning. (5) Lessons Learned in 3T Areas Using Environmental-Based Learning.